Keamanan Siber, Data Pribadi, Literasi Digital, Pengabdian Masyarakat, Edukasi - Ahmad Rifa’i; Ade Irma Purnama Sari; Nafhan Khairudin Fathin; Putri Ayu Dara Sekarwangi (CV. Multi Kreasi Media, 2022)
This community service program aims to improve digital literacy by educating the public about cybersecurity and personal data protection. In today’s digital era, the public is increasingly exposed to cybercrime risks, while awareness and understanding of digital safety remain low, especially among active internet users such as MSME actors, students, and housewives. The program was designed using a participatory-educative approach, including stages such as partner needs assessment, preparation of educational materials, interactive training, mentoring, and evaluation. The results indicated a significant improvement in participants' knowledge regarding basic cybersecurity practices, such as password management, phishing identification, and privacy settings. Tangible outputs include a training module, educational infographics, and short videos that can be reused by the community. Furthermore, the program successfully formed digital literacy agents from active participants to continue promoting cybersecurity awareness in their surroundings. The conclusion shows that community-based education effectively enhances cybersecurity awareness and provides measurable impact. Future recommendations include program replication, cross-sectoral collaboration, and development of online educational platforms for communities..